Relevansi, Asas, dan Histori Perkembangan Ilmu Tafsir - Farid, Ahmad; Arniasih, Ardilah; Utomo, Yayang Indriyani (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The Qur'an is a guide and source of law for Muslims, all matters in the Qur'an are admonitions for mankind to obtain salvation in the world and hereafter. Since the time of Prophet Muhammad (peace be upon him), tafsir has been an integral part in understanding and explaining the teachings of the Qur'an. Over time, the science of exegesis developed and gave rise to various methods and approaches of interpretation, such as tafsir ijtihad, tahlīliy, ijmāliy, muqāran, maudhu'i. The science of exegesis plays an important role in understanding the laws of the Qur'an and how to apply them in everyday life. This research is designed with qualitative methods, data collection using documentary studies, data analysis procedures using data collection steps, data cleaning, analyzing data, and interpreting results. The results of this study are explaining the science of interpretation which has a great role in knowing the meaning of the Qur'an, the principle of the science of interpretation which is the recommendation of Muslims to learn it and, the history of the science of interpretation that has begun since the time of the prophet Muhammad and also the first interpreter of the Qur'an until the science of interpretation continues today which has emerged various methods of interpreting the Qur'an. Limited time, cost, energy make this research no longer optimal also the lack of sources and data analysis obtained is still small making the results of this study less contain many opinions from various other sources. This research is far from perfect, so for the next research it is expected to be better than before